2022
DOI: 10.1371/journal.pone.0270714
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte mitochondrial DNA copy number is a potential non-invasive biomarker for psoriasis

Abstract: Abnormalities in the mitochondria have been linked to psoriasis, a chronic immune-mediated inflammatory skin disease. The mitochondrial DNA (mtDNA) is present in thousands of copies per cell and altered mtDNA copy number (mtDNA-CN), a common indicator of mitochondrial function, has been proposed as a biomarker for several diseases including autoimmune diseases. In this case–control study, we investigated whether the mtDNA-CN is related to psoriasis, correlates with the disease duration and severity, and can se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…no. 51304; Qiagen GmbΗ) according to the manufacturer's instructions as previously described ( 24 ). Briefly, a mixture of 200 µl buffy coat, 20 µl protease and 200 µl lysis buffer was incubated at 56˚C for 10 min and then centrifuged at 20,000 x g for 1 min at 4˚C.…”
Section: Methodsmentioning
confidence: 99%
“…no. 51304; Qiagen GmbΗ) according to the manufacturer's instructions as previously described ( 24 ). Briefly, a mixture of 200 µl buffy coat, 20 µl protease and 200 µl lysis buffer was incubated at 56˚C for 10 min and then centrifuged at 20,000 x g for 1 min at 4˚C.…”
Section: Methodsmentioning
confidence: 99%
“…A 2022 study also found that the mtDNA copy number is a potential biomarker for psoriasis [ 58 ]. In the case–control study, mtDNA copy number was significantly decreased in patients with psoriasis compared to healthy controls.…”
Section: Mitochondria Dysfunction and Dermatological Manifestationsmentioning
confidence: 99%
“…Sub-group analysis revealed that mtDNA copy number was significantly lower in patients with a longer psoriasis diagnosis and significantly lower in patients with higher disease severity. The study suggests that mtDNA copy number can be a non-invasive biomarker for early detection of psoriasis [ 58 ].…”
Section: Mitochondria Dysfunction and Dermatological Manifestationsmentioning
confidence: 99%
“…41 In another study, a low mtDNA copy number was suggested to be utilized as a blood-based biomarker for early psoriasis diagnosis. 42 Therianou at el isolated mtDNA from serum of psoriasis patients, whereas few studies also report that damage to mitochondria could actually benefit these patients. Similarly, in androgenetic alopecia, increased H 2 O 2 enhances TGF-β expression, hair follicle inhibitory factors, senescence and inhibits migration.…”
Section: Skin and Oxidative Stressmentioning
confidence: 99%
“…Mitochondrial dysfunction and ROS are reported to be a deciding factor in psoriasis pathogenesis 40 as even demonstrated by Hamanaka et al in his study where TFAM cKO mice were observed with compromised keratinocytes differentiation 41 . In another study, a low mtDNA copy number was suggested to be utilized as a blood‐based biomarker for early psoriasis diagnosis 42 . Therianou at el isolated mtDNA from serum of psoriasis patients, whereas few studies also report that damage to mitochondria could actually benefit these patients.…”
Section: Introductionmentioning
confidence: 97%